Cadaver Study on Variation of Nutrient Foramina of Adult Human Humeri in Bangladeshi Population (Community Based Medical Journal, 2024)
The nutrient foramen is an opening in the bone shaft which allows passage to the blood vessels of the modularly cavity of a bone for its nourishment and growth. Nutrient artery is the major source of blood supply to bone and it plays an important role in healing of fracture and trauma and is also important for bone grafting. This cross-sectional, descriptive cadaver based study aims to determine the presence, direction, common location, position and number of nutrient foramen of adult human humerus in a Bangladeshi population. One hundred samples (43 on right  and  57 on left) were selected through the purposive sampling technique which was carried out in the Department of Anatomy, Mymensingh Medical College, Bangladesh, from July 2021 to June 2022. Any damaged, unossified bones or fractured bones were excluded. The presence of nutrient foramina was observed in the shaft of the humeri. Data were recorded and tabulated to analyze using Microsoft Excel and SPSS software. Nutrient foramina was found in all the samples on both sides. So nutrient foramina present on the right side was 100% and on the left side was 100%. The direction of nutrient foramina towards the elbow joint was found in all the samples of both sides. Among 43 right humeri, 37(75.51%) have single-nutrient foramen and 06(24.49%) have double-nutrient foramina. Among 57 left humeri, 53(92.98%) have single nutrient foramen, 03(5.27%) have double nutrient foramina and 01(1.75%) has triple nutrient foramina. In case of location of nutrient foramina, among 49 right nutrient foramina, 45(91.84%) were found on the anteromedial surface, 02(4.08%) were found on the anterolateral surface and 02(4.08%) were on the posterior surface of the shaft of the humerus. In case of 62 left nutrient foramina, 57(91.94%) were found on the anteromedial surface and 05(8.06%) were found on the posterior surface of the shaft of the humerus. In case of position of nutrient foramina, among 49 right nutrient foramina, 01(2.04%) was found on the upper third, 46(93.88%) on the middle third and 02(4.08%) on the lower third of the shaft of the humerus. In case of 62 left nutrient foramina, 01(1.60%) was on the upper third, 57(91.95%) were on the middle third and 04(6.45%) were on the lower third of the shaft of the humerus.CBMJ 2024 July: vol. 13 no. 02 P: 176-182